(untitled) (Eurasian Medical Research Periodical, 2023)
With thrombocytopenic purpura, there is a violation of the formation of thromboplastin and serotonin, a decrease in contractility and an increase in the permeability of the capillary wall. This is associated with prolongation of bleeding time, violation of the processes of thrombosis and retraction of the blood clot. With hemorrhagic exacerbations, the number of platelets decreases down to single cells in the preparation, during the period of remission it is restored to a level below the norm